Haematocrit Patterns following Transurethral Resection of Prostate for Benign Prostatic Hyperplasia among Jehovah’s Witnesses - Raphael, John E.; Nwabuko, Ogbonna (British Journal of Healthcare and Medical Research, 2022)
Background: Transurethral resection of the prostate (TURP) is a gold standard surgical intervention for managing symptomatic benign prostatic hyperplasia (BPH) due to its minimal blood loss benefit, especially when dealing with patients that do not consent to blood transfusion. However, there is still a dilemma on the efficacy of this procedure as a preferable choice in minimising blood loss. This study aimed to highlight the pattern of haematocrit levels of Jehovah’s Witnesses’ subjects with BPH following TURP. Methodology: This is a retrospective study of sixty-seven Jehovah’s Witnesses patients with BPH who underwent TURP at the University of Port Harcourt Teaching Hospital and a private hospital from January 2009 to January 2021. Their venous pre-operative haematocrit levels were measured a day before TURP and on a postoperative day 3. Overall blood loss was estimated by subtracting the post-operative packed cell volume (post-ops PCV) from Pre-operative Packed cell volume (Pre-ops PCV) [Overall Blood Loss (%)= post-ops PCV – Pre-ops PCV]. Estimated Blood Loss (ml) = Overall Blood Loss (%) divided by 3% multiplied by 450 ml. Results: Mean age of the study population who underwent TURP was 68.05±8.4 years, while the mean pre-and post-operative haematocrit levels were 35.65±6.5% and 31.44±4.3 %, respectively. There was an age-independent significant association between the pre-and post-operative haematocrit levels (P=0.0004). The pre-operative haematocrit levels significantly reduced with age and increased in the younger age group, while the post-operative haematocrit level did not change significantly with age (P=0.019 and P=0.19 respectively). The net blood loss of BPH patients below their sixties was considerably higher than the amount lost in their BPH counterparts above their sixties (P=0.014). Conclusion: Although TURP is a preferable choice in the surgical management of clinical BPH, bleeding is still one of the possible complications. The younger age group (those below their sixties) are more prone to blood loss using this intervention. Hence, it is a more preferable choice for managing BPH in the elderly. A subsequent study will provide a more robust population size and working variables for validation and generalization of the results.